2020
DOI: 10.1021/acs.jchemed.0c00761
|View full text |Cite
|
Sign up to set email alerts
|

How the COVID-19 Pandemic Changed Chemistry Instruction at a Large Public University in the Midwest: Challenges Met, (Some) Obstacles Overcome, and Lessons Learned

Abstract: This communication presents a partial historical summary of some of Iowa State University’s Chemistry Department teaching response to the shift to online course delivery caused by the COVID-19 pandemic. The observations reflect discussions between and informal surveys of an instructor cohort that impacted roughly 1200 undergraduate students. These students were enrolled in general chemistry I, organic chemistry II, inorganic chemistry, quantum mechanics, and chemistry for non-physical-science majors. The paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 3 publications
1
22
0
2
Order By: Relevance
“…Students who had not planned to study at home suddenly no longer had access to university spaces and may have faced challenges such as increased care responsibilities, work, or competition for technological resources (e.g., only one laptop shared between multiple users in the home) as well as unequal access to good Internet depending on their resources and home location, these issues have also been found by Burnett et al. (2020) with students studying in USA and Hallal et al. (2020) teaching students in Lebanon.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Students who had not planned to study at home suddenly no longer had access to university spaces and may have faced challenges such as increased care responsibilities, work, or competition for technological resources (e.g., only one laptop shared between multiple users in the home) as well as unequal access to good Internet depending on their resources and home location, these issues have also been found by Burnett et al. (2020) with students studying in USA and Hallal et al. (2020) teaching students in Lebanon.…”
Section: Introductionmentioning
confidence: 85%
“…Although online learning has previously opened up opportunities to many students worldwide and increased accessibility (Appana, 2008), this particular shift exacerbated inequalities among students in many cases. Students who had not planned to study at home suddenly no longer had access to university spaces and may have faced challenges such as increased care responsibilities, work, or competition for technological resources (e.g., only one laptop shared between multiple users in the home) as well as unequal access to good Internet depending on their resources and home location, these issues have also been found by Burnett et al (2020) with students studying in USA and Hallal et al (2020) teaching students in Lebanon. For ecology and aligned disciplines, the move online had additional challenges.…”
Section: Introductionmentioning
confidence: 99%
“…An initial consideration when implementing enforced 'emergency' online teaching is whether lecture material should be provided in synchronous or asynchronous form. Jeffery and Bauer (2020) reported that students found it more difficult to maintain attention during synchronous online lectures than in in-person lectures, while Lee (2020) Burnett et al (2020) and Petillion & McNeill (2020b) suggested that asynchronous online lecture content provides learning benefits compared with synchronous online lecture delivery, with the latter noting similar advantages to those identified in the present study i.e. flexibility, control of pace, and the ability to review content.…”
Section: Implications For Practicementioning
confidence: 49%
“…According to the previous survey, classroom teaching was replaced by online teaching and learning in African, American, Asia-Pacific, and European regions by 29%, 72%, 60%, and 85%, respectively. Clearly, the life of university staff and students became harder as many new challenges arose [2][3][4][5], mainly in medical education [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%